2012
DOI: 10.1074/jbc.m111.311142
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanism for FcϵRI-mediated Signal Transducer and Activator of Transcription 5 (STAT5) Tyrosine Phosphorylation and the Selective Influence of STAT5B over Mast Cell Cytokine Production

Abstract: Background: STAT5 is a transcription factor that is vital for mast cell function. Results: Loss of Fyn kinase prevents, whereas loss of Lyn, Gab2, or SHP-1 enhances, Fc⑀RI-mediated STAT5 tyrosine phosphorylation. Conclusion: IgE-mediated STAT5 activation in mast cells requires Fyn kinase.Significance: Elucidating the mechanisms of mast cell activity is essential to understanding and treating allergic pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 42 publications
(63 reference statements)
3
42
1
Order By: Relevance
“…We recently found that Stat5, activated by Fyn kinase, is critical for IgE-mediated signaling (22, 23). In addition to Fyn and Stat5, FcεRI activates Syk kinase, which, along with Fyn, induces Akt activation (33).…”
Section: Resultsmentioning
confidence: 99%
“…We recently found that Stat5, activated by Fyn kinase, is critical for IgE-mediated signaling (22, 23). In addition to Fyn and Stat5, FcεRI activates Syk kinase, which, along with Fyn, induces Akt activation (33).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that activation of mast cells resulted in the rapid tyrosine phosphorylation of several transcription factors. We selected STAT5, which has been extensively studied in FcεRI-or KIT-activated cells (53,54), as the transcription factor. To elucidate the role of PAG in this process, we examined tyrosine phosphorylation of STAT5 in nonactivated and antigen-or SCF-activated PAG-WT and PAG-KO cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In SCF-activated cells, KIT activates STAT5 partly through the tyrosine kinase JAK2 (69). In contrast, JAK2 is dispensable in IgE-activated cells, which use FYN for STAT5 phosphorylation (53). Phosphorylated STAT5 serves as a transcription factor for a number of inflammatory genes (55).…”
Section: Discussionmentioning
confidence: 99%
“…6A, 6B). Recently, the FynStat5B pathway has been reported to be a novel mechanism for FcεRI-mediated cytokine production (44). The marked suppression of FcεRI-mediated cytokine production may be due not only to reduced FcεRI expression, but also to reduced transcription factor Stat5B expression (Fig.…”
Section: Discussionmentioning
confidence: 99%